2001
DOI: 10.1038/sj.leu.2402116
|View full text |Cite
|
Sign up to set email alerts
|

Differences in genetic changes between multiple myeloma and plasma cell leukemia demonstrated by comparative genomic hybridization

Abstract: To analyze the genomic differences between multiple myeloma (MM) and plasma cell leukemia (PCL), a total of 30 cases were studied by comparative genomic hybridization (CGH). In five cases with a low proportion of plasma cells (PC) in bone marrow, an enrichment of PC was performed by using immunomagnetic beads conjugated with the monoclonal antibody B-B4. In 24 out of the 25 MM (96%) and in all five PCL (100%) patients DNA copy number changes were identified by CGH analysis; in the MM case without chromosomal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 27 publications
3
42
0
1
Order By: Relevance
“…In fact, CGH has proved to be the most robust technique for identification of the total number of chromosome imbalances. [19][20][21][22] This is the first report that shows a prognostic impact of genomic imbalances detected by CGH in MM. Both the presence of genomic changes and the detection of genetic losses were associated with a significant decrease in survival compared with patients without such characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, CGH has proved to be the most robust technique for identification of the total number of chromosome imbalances. [19][20][21][22] This is the first report that shows a prognostic impact of genomic imbalances detected by CGH in MM. Both the presence of genomic changes and the detection of genetic losses were associated with a significant decrease in survival compared with patients without such characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…22 Calculation of the tumor DNA to normal DNA fluorescence ratios along the length of each chromosome was performed by means of an automated CGH software package (Applied Imaging, Sunderland, United Kingdom). Ratio values obtained from at least 10 metaphase cells for each case were averaged.…”
Section: Comparative Genomic Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Partial or full monosomy of 13 chromosome is usually found in B-cell chronic lymphocytic leukemia 36 and multiple myeloma patients. [37][38][39][40] In NHL, the frequencies of losses on 13q ranged from 4% in follicular lymphomas 23 to 49% in MCL. 7 Gains on 12q as well as losses on 13q have been reported as most frequent in cases with aggressive histopathologic features.…”
Section: Discussionmentioning
confidence: 99%
“…13 Previously comparative genomic hybridization studies have shown that gains of chromosome 1q consistently involving the 1q21 region is one of the most common genetic abnormalities in MM. [14][15][16] Gain of 1q21 can occur as isochromosomes, duplications or jumping translocations in MM. 17,18 Many of these chromosome changes are structural and do not involve copy number changes.…”
Section: Introductionmentioning
confidence: 99%